Seralogic studies on ineidence of bluetongue disease of sheep in elazığ, diyarbakır and Şanlıurfa - Yusuf BOLAT (Eurasian Journal of Veterinary Sciences)
Pericipitating antibody with the aid of immunodiffusion test and neutralizing antibody against bluetongue virus type 4 were determined in 275 of 1290 sera samples from sheep which in same cities of the east south- east Anatolia such as Elazıg, Diyarbakır, Şanlıurfa, Gaziantep, Kayseri, Muş, Van and Tunceli. The ineidence of the disease in these cities was determined as 21.32 percent.